Psychiatric comorbidities in opioid-dependent patients undergoing a replacement therapy programme in Spain: The PROTEUS study. (30th September 2016) - Roncero, Carlos; Barral, Carmen; Rodríguez-Cintas, Laia; Pérez-Pazos, Jesús; Martinez-Luna, Nieves; Casas, Miguel; Torrens, Marta; Grau-López, Lara
Abstract: Opioid-dependent patients show a high rate of psychiatric comorbidities. The prevalence and characteristics of patients with dual diagnosis have not been well established in Spanish opioid agonist treatment (OAT) programmes. Thus, 621 opioid-dependent patients enrolled in OAT programmes were assessed, using the EuropASI questionnaire, for psychiatric comorbidities, which were detected in 67% of patients (anxiety 53%, mood disorders 48%, sleep disorders 41%, substance-related disorders 36%). In addition, compared with patients without a dual diagnosis, patients with dual pathology were significantly older, used benzodiazepines and cannabis in significantly greater percentages, and showed significantly more frequent infectious and non-infectious comorbidities, worse overall working status, a lower proportion of drivers and higher levels of severity regarding medical, employment, alcohol, legal, family and psychological issues. Therefore, the data showed a very high prevalence of psychiatric comorbidity in opioid-dependent patients receiving OAT in Spain and several problems frequently associated with patients with dual diagnosis. Physicians treating opioid-dependent patients should be aware of these facts to correctly identify and manage patients with a dual diagnosis. Highlights: In total, 621 OD patients in Spanish OAT programmes were assessed for psychiatric comorbidities. Psychiatric comorbidities were detected in 67% of patients. Dual patients showed more infectious and non-infectious comorbidities than non-dual patients. Dual patients showed worse working status and a higher severity of problems. Dual patients were older and used benzodiazepines and cannabis more frequently.